2018
DOI: 10.1002/mnfr.201800713
|View full text |Cite
|
Sign up to set email alerts
|

Nutritionally Derived Metabolic Cues Typical of the Obese Microenvironment Increase Cholesterol Efflux Capacity of Adipose Tissue Macrophages

Abstract: Background Cholesterol retention within plasma membranes of macrophages is associated with increased inflammatory signaling. Cholesterol efflux via the transporters ABCA1, ABCG1, and SR‐BI to high‐density lipoprotein (HDL) particles is a critical mechanism to maintain cellular cholesterol homeostasis. Little is known about the impact of the obese microenvironment on cholesterol efflux capacity (CEC) of macrophages. In this study, the CEC of obese‐derived primary adipose‐tissue macrophages (ATM) is evaluated an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
8
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 26 publications
1
8
0
Order By: Relevance
“…For instance, Abca1/g1 expression is enhanced in lipid-laden, MMe ATM vs. lean ATM [7]. This is coherent with the observation that while Chol efflux capacity to ApoA-1 was significantly reduced in M1 ATM, it was surprisingly enhanced in primary obese and in vitro polarized MMe ATM [9]. This could be associated with a protective mechanism in which lipid-laden ATMs promote Chol efflux to lower inflammation, but are ultimately overwhelmed by the lipid charge.…”
Section: Lipid Efflux/exportsupporting
confidence: 80%
See 1 more Smart Citation
“…For instance, Abca1/g1 expression is enhanced in lipid-laden, MMe ATM vs. lean ATM [7]. This is coherent with the observation that while Chol efflux capacity to ApoA-1 was significantly reduced in M1 ATM, it was surprisingly enhanced in primary obese and in vitro polarized MMe ATM [9]. This could be associated with a protective mechanism in which lipid-laden ATMs promote Chol efflux to lower inflammation, but are ultimately overwhelmed by the lipid charge.…”
Section: Lipid Efflux/exportsupporting
confidence: 80%
“…Metabolically activated (MMe) ATMs are part of a rather new concept of an activation profile that was introduced by Kratz et al, and distinguishes them both functionally and phenotypically from the M1 and M2 phenotypes [7,8]. More importantly, MMe ATMs present significant changes in their intrinsic metabolism, including lipid mobilization (i.e., lysosomal catabolism, storage within lipid droplets (LDs) and efflux) and utilization (i.e., free fatty acids (FFA)/Chol synthesis and oxidation for energy production or membrane incorporation) [9][10][11]. On this account, the emerging fields of lipidomics and metabolomics have proven key in the study of ATM function in regard to individual lipid species.…”
Section: Introductionmentioning
confidence: 99%
“…LPS-induced obesity has also been causally linked to the binding of scavenger receptor type B (SR-BI) (Hersoug et al, 2016). These binding products enhanced LPS' actions (i.e., promoted the transport of lipoproteins on the endothelial barrier and the endocytosis of adipocytes), accelerated the transformation of macrophages from M2 type to M1 type in adipose tissue, and mediated inflammatory reactions (Xiong et al, 2018;O'Reilly et al, 2019). In addition, it has been shown that LPS contributes to the expression of receptor protein mRNA that is related to angiotensin receptors, and that this expression was positively correlated with specific bacteria in the gut (Oliveira et al, 2020).…”
Section: Gut Microbiota Dysbiosis Can Increase the Absorption Of Lipopolysaccharide And Cause Inflammationmentioning
confidence: 99%
“…Petkevicius et al demonstrated that ATM isolated from obese mice and humans exhibited increased rate of de novo phosphatidylcholine (PC) biosynthesis [ 28 ]. Consistently, the cholesterol efflux capacity (CEC) was enhanced in ATM in obesity associated with increased expressions of the transporters like ABCA1 compared to that of lean mice [ 29 ].…”
Section: Remodeling Of Atm In Obesitymentioning
confidence: 99%